LAYERED TRIMETALLIC CATALYST ARTICLES AND METHODS FOR MAKING CATALYST ARTICLES - Patent application

A layered catalyst design with palladium and platinum in separate layers addresses the cost issue of TWC catalysts by maintaining performance, enhancing CO, HC, and NOx conversion, and reducing palladium use.

JP7608354B2Active Publication Date: 2025-01-06BASF MOBILE EMISSIONS CATALYSTS LLC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021556826
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-16
Filing Date
2020-03-18
Publication Date
2025-01-06
Estimated Expiration
2040-03-18

Smart Images

  • Figure 0007608354000003
    Figure 0007608354000003
  • Figure 0007608354000004
    Figure 0007608354000004
  • Figure 0007608354000005
    Figure 0007608354000005
Patent Text Reader

Abstract

The present invention provides a trimetallic layered catalyst article comprising a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component, a second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein the weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1:2. The present invention also provides a process for preparing the trimetallic layered catalyst article, an exhaust system for an internal combustion engine, and the use of the trimetallic layered catalyst article to purify a gaseous exhaust stream.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Application No. 62 / 819695, filed March 18, 2019, and European Application No. 19169497.5, filed April 16, 2019.

[0002] The invention as claimed relates to layered catalyst articles useful in the treatment of exhaust gases to reduce pollutants contained therein. In particular, the invention as claimed relates to layered trimetallic catalyst articles and methods of preparing the catalyst articles. [Background technology]

[0003] Three-way conversion (TWC) catalysts (hereinafter referred to interchangeably as three-way conversion catalysts, three-way catalysts, TWC catalysts, and TWC) have been utilized for several years to treat exhaust gas streams from internal combustion engines. Typically, catalytic converters containing three-way conversion catalysts are used in the exhaust gas lines of internal combustion engines to treat or purify exhaust gases containing pollutants such as hydrocarbons, nitrogen oxides, and carbon monoxide. Three-way conversion catalysts are typically known to oxidize unburned hydrocarbons and carbon monoxide and reduce nitrogen oxides.

[0004] Typically, most of the commercially available TWC catalysts contain palladium as the main platinum group metal component, along with a small amount of rhodium. Due to the large amount of palladium used in the creation of catalytic converters that help to reduce the amount of exhaust gas pollutants, it is possible that a shortage of palladium supply in the market may occur in the coming years. Currently, palladium is approximately 20-25% more expensive than platinum. At the same time, due to the decline in platinum demand, platinum prices are expected to decline. One of the reasons may be the decline in the production of diesel vehicles.

[0005] It would therefore be desirable to replace a portion of the palladium with platinum in the TWC catalyst in order to substantially reduce the cost of the catalyst, however the proposed approach is complicated by the need to maintain or improve the desired efficacy of the catalyst, which may not be possible by simply replacing a portion of the palladium with platinum.

[0006] Therefore, the focus of the claimed invention is on the individual CO, HC, and NO x Conversion levels, as well as non-methane hydrocarbons (NMHCs) and nitrous oxide (NO x The goal of this study is to provide a catalyst in which approximately 50% of the palladium is replaced by platinum without compromising overall catalyst performance, as described by a comparison of abbreviated tailpipe emissions of 100% platinum and 100% platinum-Pt alloys, which is one of the key requirements for vehicle approval by regulatory bodies in most jurisdictions. Summary of the Invention

[0007] The claimed invention provides a trimetallic (Pt / Pd / Rh) layered catalyst article comprising a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component, a second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein the weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1.0:2.0, the first layer being deposited on the substrate and the second layer being deposited on the first layer. In one embodiment, the weight ratio of palladium to platinum is in the range of 1.0:0.7 to 1.0:1.3. In one embodiment, the weight ratio of palladium to platinum to rhodium is in the range of 1.0:0.7:0.1 to 1.0:1.3:0.3.

[0008] In one embodiment, the first layer is essentially free of platinum and rhodium. In one embodiment, the second layer may further comprise palladium supported on an alumina component.

[0009] In another aspect of the claimed invention, there is provided a process for preparation of a layered catalyst article, the process comprising preparing a first layer slurry, depositing the first layer slurry on a substrate to obtain the first layer, preparing a second layer slurry, and depositing the second layer slurry on the first layer to obtain the second layer followed by calcination at a temperature in the range of 400-700°C, wherein the step of preparing the first layer slurry or the second layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation, and post-addition.

[0010] The claimed invention in yet another aspect provides an exhaust system for an internal combustion engine, the system comprising a layered catalyst article of the invention.

[0011] The claimed invention also provides a method of treating a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides, the method comprising contacting the exhaust stream with a layered catalyst article or an exhaust system in accordance with the invention. The claimed invention further provides a method of reducing the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a layered catalyst article or an exhaust system in accordance with the invention to reduce the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in the exhaust gas. [Brief description of the drawings]

[0012] To provide an understanding of embodiments of the present invention, reference is made to the accompanying drawings, which are not necessarily drawn to scale, and in which reference numerals refer to components of exemplary embodiments of the present invention. The drawings are merely illustrative and should not be construed as limiting the present invention. The above and other features of the claimed invention, their nature and various advantages will become more apparent upon consideration of the following detailed description in conjunction with the accompanying drawings. [Figure 1] 1 is a schematic diagram of a catalytic article design in an exemplary configuration according to some embodiments of the claimed invention. [Diagram 2]1 is a schematic diagram of an exhaust system according to some embodiments of the claimed invention. [Figure 3A] 1 is a line graph showing comparative test results for cumulative THC emissions, NO emissions, and CO emissions for catalyst B of the present invention and a reference catalyst. [Figure 3B] 1 is a line graph showing comparative test results for cumulative THC emissions, NO emissions, and CO emissions for catalyst B of the present invention and a reference catalyst. [Figure 3C] 1 is a line graph showing comparative test results for cumulative THC emissions, NO emissions, and CO emissions for catalyst B of the present invention and a reference catalyst. [Figure 4A] 1 illustrates a line graph showing comparative test results for cumulative HC emissions in midbed and tailpipe for inventive catalyst A and a reference catalyst. [Figure 4B] 1 illustrates a line graph showing comparative test results for cumulative CO emissions in midbed and tailpipe for inventive catalyst A and a reference catalyst. [Figure 4C] 1 illustrates a line graph showing comparative test results for cumulative NO emissions in midbed and tailpipe for inventive catalyst A and a reference catalyst. [Figure 5A] 1 is a line graph showing comparative test results for cumulative CO, NO, and THC emissions for catalysts C, D, E, and a reference catalyst. [Figure 5B] 1 is a line graph showing comparative test results for cumulative CO, NO, and THC emissions for catalysts C, D, E, and a reference catalyst. [Figure 5C] 1 is a line graph showing comparative test results for cumulative CO, NO, and THC emissions for catalysts C, D, E, and a reference catalyst. [Figure 6A] 1 is a perspective view of a honeycomb-shaped substrate support that may include a catalyst composition according to one embodiment of the claimed invention. [Figure 6B] 6B is a partial cross-sectional view enlarged relative to FIG. 6A and taken along a plane parallel to an end face of the substrate support of FIG. 6A, showing an enlarged view of a number of gas flow passages shown in FIG. 6A. [Figure 7]6B is a cutaway view of an enlarged section relative to FIG. 6A, in which the honeycomb-shaped substrate in FIG. 6A represents a wall-flow filter substrate monolith. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will now be described more fully below. The present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the disclosed materials and methods.

[0014] In the context of describing the materials and methods discussed herein (particularly in the context of the claims which follow), the use of the terms "a," "an," "the," and similar directives are intended to cover both the singular and the plural, unless otherwise indicated in the specification or clearly contradicted by context.

[0015] The term "about" is used throughout this specification to describe and account for small variations. For example, the term "about" refers to ±5% or less, e.g., ±2% or less, ±1% or less, ±0.5% or less, ±0.2% or less, ±0.1% or less, or ±0.05% or less. All numerical values ​​are modified by the term "about" whether or not expressly stated. Of course, values ​​modified by the term "about" include the specific value. For example, "about 5.0" must include 5.0.

[0016] All methods described herein can be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "etc.") provided herein is intended only to better describe the materials and methods and is not intended to be limiting in scope unless otherwise claimed.

[0017] The present invention provides a trimetallic layered catalyst article comprising three platinum group metals (PGMs) in which a large amount of platinum can be used to substantially replace palladium.

[0018] Platinum group metal (PGM) refers to any component that includes a PGM (Ru, Rh, Os, Ir, Pd, Pt, and / or Au). For example, the PGM may be in a metallic form with a zero valence, or the PGM may be in an oxide form. Reference to a "PGM component" allows for the presence of the PGM in any valence state. Terms such as "platinum (Pt) component," "rhodium (Rh) component," "palladium (Pd) component," "iridium (Ir) component," "ruthenium (Ru) component," and the like refer to the respective platinum group metal compounds, complexes, and the like that decompose or otherwise convert to a catalytically active form, typically a metal or metal oxide, upon calcination or use of the catalyst.

[0019] In one embodiment, palladium and platinum are provided in separate layers to avoid the formation of alloys that may limit the efficacy of the catalyst under certain conditions. The formation of alloys may result in the formation of a core-shell structure, excessive PGM stabilization, and / or sintering. The best performance of the catalyst article is seen when palladium is provided in the bottom layer and platinum and rhodium are provided in the top layer, i.e., physical separation of platinum and palladium in different washcoat layers allows for improved performance. In another embodiment, platinum and palladium are provided in the same layer, e.g., the top layer, and either platinum or palladium, or both, are thermally or chemically fixed onto the support prior to slurry preparation. In the context of the present invention, the term "first layer" is used interchangeably with "bottom layer" or "bottom coat", while the term "second layer" is used interchangeably with "top layer" or "top coat". The first layer is deposited on the substrate and the second layer is deposited on the first layer.

[0020] The terms "catalyst", "catalytic article", or "catalyst article" refer to a component in which a substrate is coated with a catalytic composition used to promote a desired reaction. In one embodiment, the catalytic article is a layered catalytic article. The term layered catalytic article refers to a catalytic article in which a substrate is coated with a PGM composition in a layered manner. These compositions may be referred to as washcoats.

[0021] "NO x " refers to nitrogen oxide compounds such as NO and / or NO2.

[0022] The platinum group metal is supported or impregnated on a support material such as an alumina component, an oxygen storage component, etc. As used herein, "impregnated" or "impregnation" refers to the infiltration of the catalytic material into the porous structure of the support material.

[0023] "Support" in the context of a catalytic material or composition or catalytic washcoat refers to a material that receives metals (e.g., PGMs), stabilizers, promoters, binders, etc. by precipitation, association, dispersion, impregnation, or other suitable methods. Exemplary supports include refractory metal oxide supports as described herein below.

[0024] "Refractory metal oxide supports" are metal oxides including, for example, bulk alumina, ceria, zirconia, titania, silica, magnesia, neodymia, and other materials known for such use, as well as physical mixtures or chemical combinations thereof, including atomically doped combinations, and including active compounds such as high surface area or activated aluminas.

[0025] Exemplary combinations of metal oxides include alumina-zirconia, alumina-ceria-zirconia, lanthana-alumina, lanthana-zirconia-alumina, baria-alumina, baria-lanthana-alumina, baria-lanthana-neodymia alumina, and alumina-ceria. Exemplary aluminas include large pore boehmite, gamma-alumina, and delta / theta alumina. Useful commercially available aluminas used as starting materials in the exemplary process include activated aluminas, such as high bulk density gamma-alumina, low or medium bulk density large pore gamma-alumina, and low bulk density large pore boehmite and gamma-alumina. Such materials are generally believed to provide durability to the resulting catalyst.

[0026] The term "high surface area refractory metal oxide support" specifically refers to support particles having pores greater than 20 Å and a broad pore distribution. High surface area refractory metal oxide supports, such as alumina support materials also called "gamma alumina" or "activated alumina", typically have a surface area of ​​60 m2 per gram ("m 2 / g), often up to about 300m 2 / g or more of virgin material. Such activated aluminas are typically mixtures of gamma and delta phases of alumina, but may also contain significant amounts of eta, kappa, and theta alumina phases.

[0027] Accordingly, the present invention provides a trimetallic layered catalyst article comprising a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component, a second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein a weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1.0:2.0, and wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.

[0028] In one embodiment, the weight ratio of palladium to platinum is in the range of 1:0.7 to 1:1.3. In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on at least one of an oxygen storage component and an alumina component, a second layer including platinum and rhodium supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein the weight ratio of palladium to platinum is in the range of 1.0:0.7 to 1.0:1.3, the first layer being deposited on the substrate and the second layer being deposited on the first layer.

[0029] In one embodiment, the weight ratio of palladium to platinum to rhodium is between 1.0:0.7:0.1 and 1.0:1.3:0.3. In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on at least one of an oxygen storage component and an alumina component, a second layer including platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein the weight ratio of palladium to platinum to rhodium is in the range of between 1.0:0.7:0.1 and 1.0:1.3:0.3, and wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.

[0030] In one embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component, a second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein a weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1.0:2.0, the first layer being deposited on the substrate and the second layer being deposited on the first layer, the first layer comprising 80 to 100 weight percent palladium based on the total weight of palladium present in the catalyst article.

[0031] In one embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on at least one of an oxygen storage component and an alumina component, a second layer including platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein a weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1.0:2.0, the first layer being deposited on the substrate and the second layer being deposited on the first layer, the first layer being essentially free of platinum and rhodium. As used herein, the term "essentially free of platinum and rhodium" refers to the absence of exogenous addition of platinum and rhodium in the first layer, however, they may optionally be present as a fraction of <0.001%.

[0032] In one embodiment, the first layer comprises at least one alkaline earth metal oxide comprising barium oxide, strontium oxide, or any combination thereof in an amount of 1.0 to 20 wt %, based on the total weight of the first layer.

[0033] In one embodiment, a trimetallic layered catalyst article comprises a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component, a second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein a weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1.0:2.0, the first layer being deposited on the substrate and the second layer being deposited on the first layer, the second layer further comprising palladium supported on alumina, the amount of palladium being 0.1 to 20 weight percent based on the total weight of palladium present in the catalyst article.

[0034] In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on at least one of an oxygen storage component and an alumina component, a second layer including platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and palladium supported on alumina, and a substrate, wherein the weight ratio of palladium to platinum is in the range of 1.0:0.4 to 1.0:2.0. In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on at least one of an oxygen storage component and an alumina component, a second layer including platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconia component, and palladium supported on the alumina component, and a substrate, wherein the weight ratio of palladium to platinum is in the range of 1.0:0.7 to 1.0:1.3, and the first layer is deposited on the substrate and the second layer is deposited on the first layer.

[0035] In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer comprising i) palladium supported on at least one of an oxygen storage component and an alumina component, and ii) barium oxide; a second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component, a zirconia component, and palladium supported on the alumina component; and a substrate, wherein a weight ratio of palladium to platinum is in the range of 1.0:0.7 to 1.0:1.3, the first layer being deposited on the substrate and the second layer being deposited on the first layer.

[0036] In one embodiment, the zirconia component comprises at least 70% zirconia.

[0037] In one embodiment, the platinum and / or palladium is thermally or chemically immobilized.

[0038] In one embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component, a second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component, a zirconia component, and palladium supported on the alumina component, and a substrate, wherein a weight ratio of palladium to platinum is in the range of 1.0:0.7 to 1.0:1.3, and the platinum and / or palladium present in the second layer is thermally or chemically immobilized, and wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.

[0039] In one embodiment, the trimetallic layered catalyst article comprises a catalyst layer comprising 1.0 to 300 g / ft supported on an alumina component and an oxygen storage component. 3 A first layer loaded with palladium of 1.0 to 100 g / ft 3 of rhodium and 1.0-300g / ft 3 and a second layer loaded with platinum, each supported on an oxygen storage component and / or a zirconia component, wherein the first layer is deposited on a substrate and the second layer is deposited on the first layer.

[0040] In one embodiment, rhodium is present in an amount of 4.0 to 12 g / ft 3 In one exemplary embodiment, rhodium is used in an amount of 4 g / ft 3 In one embodiment, palladium is used in an amount of 20 to 80 g / ft 3 In one exemplary embodiment, palladium is used in an amount of 38 g / ft 3 In one embodiment, platinum is used in an amount of 20 to 80 g / ft 3 In one embodiment, platinum is used in an amount of 38 g / ft 3 is used in amounts of

[0041] In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on an oxygen storage component and an alumina component, and a second layer comprising rhodium and platinum supported on the oxygen storage component and palladium supported on the alumina component, where the first layer is deposited on a substrate and the second layer is deposited on the first layer.

[0042] In one of the preferred embodiments, the weight ratio of palladium to platinum is 1.0:1.0. In one exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on at least one of an oxygen storage component and an alumina component, a second layer including platinum and rhodium supported on at least one of an oxygen storage component and a zirconia component, and a substrate, wherein the weight ratio of palladium to platinum is in the range of 1.0 to 1.0, the first layer being deposited on the substrate, and the second layer being deposited on the first layer.

[0043] In another exemplary embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on an oxygen storage component and an alumina component, and a second layer comprising rhodium and platinum, each supported on the oxygen storage component, and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, the first layer being deposited on a substrate and the second layer being deposited on the first layer. In another exemplary embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on an oxygen storage component and an alumina component, and a second layer comprising rhodium and platinum, each supported on the oxygen storage component, and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, the first layer being deposited on a substrate and the second layer being deposited on the first layer, and the platinum and / or palladium present in the second layer being thermally or chemically immobilized.

[0044] In another exemplary embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on an oxygen storage component and an alumina component, and barium oxide, and a second layer comprising rhodium and platinum, each supported on an oxygen storage component, and palladium supported on an alumina component, wherein a weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on a substrate and the second layer is deposited on the first layer.

[0045] In another exemplary embodiment, a trimetallic layered catalyst article includes a first layer comprising palladium supported on an oxygen storage component and an alumina component, and barium oxide, and a second layer comprising rhodium and platinum, each supported on an oxygen storage component, and palladium supported on an alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, and the platinum and / or palladium present in the second layer is thermally or chemically immobilized, and wherein the first layer is deposited on a substrate and the second layer is deposited on the first layer.

[0046] In yet another exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on an oxygen storage component and an alumina component, a second layer including rhodium supported on the oxygen storage component, and platinum supported on the oxygen storage component, a weight ratio of palladium to platinum is between 1.0:0.7 and 1.0:1.3, the first layer being deposited on a substrate and the second layer being deposited on the first layer. In yet another exemplary embodiment, a trimetallic layered catalyst article includes a first layer including palladium supported on an oxygen storage component and an alumina component, a second layer including rhodium supported on the oxygen storage component, and platinum supported on a zirconia component, a weight ratio of palladium to platinum is 1.0:1.0, the first layer being deposited on a substrate and the second layer being deposited on the first layer. In yet another exemplary embodiment, the first layer comprises palladium supported on the oxygen storage component and the alumina component, and the second layer comprises rhodium supported on the oxygen storage component and platinum supported on the zirconia component, the weight ratio of palladium to platinum is 1.0:1.0. In a further exemplary embodiment, the trimetallic layered catalyst article comprises a first layer comprising palladium supported on the oxygen storage component and the alumina component, and barium oxide, and a second layer comprising rhodium supported on the oxygen storage component and platinum supported on the zirconia component, the weight ratio of palladium to platinum is 1.0:1.0, the first layer being deposited on a substrate and the second layer being deposited on the first layer.

[0047] In one exemplary embodiment, the trimetallic layered catalyst article includes a first layer including palladium supported on both the oxygen storage component and the alumina component and barium oxide, and a second layer including rhodium and platinum supported on the oxygen storage component and palladium supported on the alumina component, the weight ratio of palladium to platinum is 1.0:1.0, the first layer being deposited on a substrate and the second layer being deposited on the first layer. In another exemplary embodiment, the trimetallic layered catalyst article includes a first layer including palladium supported on both the oxygen storage component and the alumina component and barium oxide, and a second layer including rhodium supported on the oxygen storage component and platinum supported on the lanthana-zirconia component, the weight ratio of palladium to platinum is 1.0:1.0, the first layer being deposited on a substrate and the second layer being deposited on the first layer.

[0048] In one exemplary embodiment, the trimetallic layered catalyst article comprises 30.4 g / ft 3 supported on both the oxygen storage component and the alumina component. 3 of palladium, and a first layer including barium oxide and 4.0 g / ft 3 of rhodium and 38g / ft 3 of platinum, and 7.6 g / ft 3 and a second layer comprising palladium of 1000 .mu.m, wherein the first layer is deposited on a substrate and the second layer is deposited on the first layer.

[0049] In one exemplary embodiment, the trimetallic layered catalyst article comprises 38 g / ft 3 supported on both the oxygen storage component and the alumina component. 3 of palladium, and a first layer including barium oxide and 4 g / ft 3 Rhodium and lanthanide supported on zirconia component at 38 g / ft 3 and a second layer comprising platinum, wherein the first layer is deposited on a substrate and the second layer is deposited on the first layer.

[0050] As used herein, the term "oxygen storage component" (OSC) refers to an entity that has multiple valence states and can actively react with reducing agents such as carbon monoxide (CO) and / or hydrogen under reducing conditions and then react with oxidizing agents such as oxygen or nitrogen oxides under oxidizing conditions. Examples of oxygen storage components include ceria composites optionally doped with early transition metal oxides, particularly zirconia, lanthana, praseodymia, neodymia, niobia, europia, samaria, ytterbia, yttria, and mixtures thereof.

[0051] In one embodiment, the oxygen storage component utilized in the first and / or second layer comprises ceria-zirconia, ceria-zirconia-lanthana, ceria-zirconia-yttria, ceria-zirconia-lanthana-yttria, ceria-zirconia-neodymia, ceria-zirconia-praseodymia, ceria-zirconia-lanthana-neodymia, ceria-zirconia-lanthana-praseodymia, ceria-zirconia-lanthana-neodymia-praseodymia, or any combination thereof, and the amount of oxygen storage component is 20-80 wt.%, based on the total weight of the first layer or second layer. In one exemplary embodiment, the oxygen storage component comprises ceria-zirconia.

[0052] In one embodiment, the alumina component comprises alumina, lanthana-alumina, ceria-alumina, ceria-zirconia-alumina, zirconia-alumina, lanthana-zirconia-alumina, baria-alumina, baria-lanthana-alumina, baria-lanthana-neodymia-alumina, or combinations thereof, and the amount of the alumina component is 10 to 90 wt %, based on the total weight of the first layer or the second layer.

[0053] In one embodiment, the oxygen storage component comprises ceria in an amount of 5.0 to 50 wt %, based on the total weight of the oxygen storage component. In one embodiment, the oxygen storage component of the first layer comprises ceria in an amount of 20 to 50 wt %, based on the total weight of the oxygen storage component. In one embodiment, the oxygen storage component of the second layer comprises ceria in an amount of 5.0 to 15 wt %, based on the total weight of the oxygen storage component.

[0054] In the context of this invention, the term zirconia component is a zirconia-based support that is stabilized or promoted by lanthana, or baria, or ceria. Examples include lanthana-zirconia, and barium-zirconia.

[0055] As used herein, the term "substrate" refers to a monolithic material, typically in the form of a washcoat containing a plurality of particles containing a catalyst composition, on which the catalyst material is disposed.

[0056] References to a "monolithic substrate" or a "honeycomb substrate" mean a unitary structure that is homogenous and continuous from the inlet to the outlet.

[0057] As used herein, the term "washcoat" has its ordinary meaning in the art of a thin, adherent coating of catalyst or other material applied to a substrate material, such as a honeycomb-type carrier member, that is sufficiently porous to permit the passage of the gas stream to be treated. A washcoat is formed by preparing a slurry containing particles of a certain solids content (e.g., 15% to 60% by weight) in a liquid vehicle, which is then coated onto the substrate and dried to provide a washcoat layer.

[0058] As used herein and as described in Heck, Ronald, and Farrauto, Robert, Catalytic Air Pollution Control, New York: Wiley-Interscience, 2002, pp. 18-19, a washcoat layer comprises a compositionally distinct layer of material disposed on the surface of a monolithic substrate or an underlying washcoat layer. In one embodiment, a substrate contains one or more washcoat layers, each of which may differ in some manner (e.g., in its physical properties, such as, for example, particle size or crystallite phase) and / or may differ in chemical catalytic function.

[0059] A catalyst article may be "virgin," meaning that the catalyst article is new and has not been exposed to any heat or thermal stress for an extended period of time. "Virgin" may also mean that the catalyst has been recently prepared and has not been exposed to any exhaust gases or high temperatures. Similarly, an "aged" catalyst article is not virgin and has been exposed to exhaust gases and high temperatures (i.e., greater than 500° C.) for an extended period of time (i.e., greater than 3 hours).

[0060] According to one or more embodiments, the substrate of the catalyst article of the present invention may be constructed of any material typically used to prepare automotive catalysts, typically comprising a ceramic or metallic monolithic honeycomb structure. In one embodiment, the substrate is a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymeric foam substrate, or a woven fiber substrate.

[0061] The substrate typically provides a plurality of walls onto which a washcoat comprising the catalyst composition described herein above is applied and adhered, thereby acting as a support for the catalyst composition.

[0062] Exemplary metal substrates include heat-resistant metals and metal alloys such as titanium and stainless steels and other alloys in which iron is a substantial or major component. Such alloys may contain one or more of nickel, chromium, and / or aluminum, the total amount of these metals advantageously comprising at least 15% by weight of the alloy, e.g., 10-25% chromium, 3-8% aluminum, and up to 20% nickel. The alloys may also contain small or trace amounts of one or more metals, such as manganese, copper, vanadium, and titanium. The surface of the metal substrate may be oxidized at high temperatures, e.g., 1000° C. or higher, to form an oxide layer on the surface of the substrate, improving the corrosion resistance of the alloy and facilitating adhesion of a washcoat layer to the metal surface.

[0063] The ceramic material used in the construction of the substrate may include any suitable refractory material, such as cordierite, mullite, cordierite-alumina, silicon nitride, zircon-mullite, spodumene, alumina-silica magnesia, zircon silicate, sillimanite, magnesium silicate, zircon, petalite, alumina, aluminosilicates, and the like.

[0064] Any suitable substrate can be used, such as a monolithic flow-through substrate having a plurality of fine, parallel gas flow passages extending from the inlet to the outlet face of the substrate such that the passages are open to fluid flow. The passages, which are essentially straight-line paths from the inlet to the outlet, are defined by walls on which a catalytic material is coated as a washcoat such that gas flowing through the passages contacts the catalytic material. The flow passages of the monolithic substrate are thin-walled channels that can be of any suitable cross-sectional shape, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, and circular. Such structures contain from about 60 to about 1200 or more gas inlet openings (i.e., "cells") per square inch (cpsi) of cross section, more commonly from about 300 to 900 cpsi. The wall thickness of the flow-through substrate can vary, with a typical range being 0.002 to 0.1 inches. A typical commercially available flow-through substrate is a cordierite substrate having a wall thickness of 6 mils at 400 cpsi, or 4 mils at 600 cpsi. However, it will be understood that the invention is not limited to a particular substrate type, material, or shape. In an alternative embodiment, the substrate may be a wall-flow substrate, with each passageway plugged by a non-porous plug at one end of the substrate body, and alternating passageways plugged at the opposite end face. This requires the gas flow to pass through the porous walls of the wall-flow substrate to reach the outlet. Such monolithic substrates may contain up to about 700 or more cpsi, such as about 100 to 400 cpsi, more typically about 200 to about 300 cpsi. The cross-sectional geometry of the cells may vary, as explained above. Wall-flow substrates typically have wall thicknesses of 0.002 to 0.1 inches. Representative commercially available wall-flow substrates are constructed from porous cordierite, examples of which have 200 cpsi and 10 mil wall thickness, or 300 cpsi and 8 mil wall thickness, and wall porosity of 45 to 65%. Other ceramic materials such as aluminum titanate, silicon carbide, and silicon nitride have also been used as wall flow filter substrates, however, it will be understood that the invention is not limited to any particular substrate type, material, or shape.It should be noted that if the substrate is a wall-flow substrate, the catalyst composition, in addition to being disposed on the surface of the wall, may penetrate into the pore structure of the porous wall (i.e., partially or completely block the pore openings). In one embodiment, the substrate has a flow-through ceramic honeycomb structure, a wall-flow ceramic honeycomb structure, or a metal honeycomb structure.

[0065] As used herein, the term "stream" refers broadly to any combination of flowing gases that may contain solid or liquid particulate matter.

[0066] As used herein, the terms "upstream" and "downstream" refer to relative directions relative to the flow of engine exhaust gas stream from the engine toward the tailpipe, with the engine being in the upstream position and the tailpipe and any pollution abatement articles, such as filters and catalysts, being downstream of the engine.

[0067] 6A and 6B show an exemplary substrate 2 in the form of a flow-through substrate coated with a washcoat composition described herein. Referring to FIG. 6A, the exemplary substrate 2 has a cylindrical shape, with a cylindrical outer surface 4, an upstream end surface 6, and a corresponding downstream end surface 8 identical to end surface 6. The substrate 2 has a plurality of fine, parallel gas flow passages 10 formed therein. As seen in FIG. 6B, the passages 10 are formed by walls 12 and extend through the substrate 2 from the upstream end surface 6 to the downstream end surface 8, the passages 10 being unobstructed and allowing a fluid, e.g., gas flow, to flow longitudinally through the substrate 2 via the gas flow passages 10. As can be more easily seen in FIG. 6B, the walls 12 are sized and configured such that the gas flow passages 10 have a substantially regular polygonal shape. As shown, the washcoat composition can be applied in multiple distinct layers, if desired. In the embodiment shown, the washcoat consists of a first separate washcoat layer 14 adhered to the wall 12 of the substrate member and a second separate washcoat layer 16 coated over the first washcoat layer 14. In one embodiment, the invention is also practiced with two or more (e.g., three or four) washcoat layers and is not limited to the two layer embodiment shown.

[0068] FIG. 7 shows an exemplary substrate 2 in the form of a wall-flow filter substrate coated with a washcoat composition described herein. As seen in FIG. 7, the exemplary substrate 2 has a plurality of passages 52. The passages are tubularly surrounded by the inner wall 53 of the filter substrate. The substrate has an inlet end 54 and an outlet end 56. The passages are alternately blocked at the inlet end by inlet plugs 58 and at the outlet end by outlet plugs 60 to form a checkerboard pattern that is reversed at the inlet 54 and outlet 56. Gas flow 62 enters through the unblocked channel inlet 64, is stopped by the outlet plugs 60, and diffuses through the channel wall 53 (which is porous) to the outlet side 66. Gas cannot pass back to the inlet side of the wall because of the inlet plugs 58. The porous wall-flow filters used in the present invention have catalysis in the walls of the element that have or contain one or more catalytic materials on or in them. The catalytic material may be present only on the inlet side, only on the outlet side, on both the inlet and outlet sides of the element walls, or the walls themselves may be composed entirely or in part of the catalytic material. The present invention includes the use of one or more layers of catalytic material on the inlet and / or outlet walls of the element.

[0069] According to yet another aspect, the claimed invention provides a process for preparing a catalyst article. In one embodiment, the process comprises preparing a first layer slurry, depositing the first layer slurry on a substrate to obtain the first layer, preparing a second layer slurry, and depositing the second layer slurry on the first layer to obtain the second layer followed by calcination at a temperature in the range of 400-700° C., wherein the steps of preparing the first layer slurry or the second layer slurry comprise a technique selected from incipient wetness impregnation, incipient wetness co-impregnation, and post-addition. In one embodiment, the process comprises a prior step of thermally or chemically fixing platinum or palladium, or both, on the support.

[0070] Thermal setting involves, for example, deposition of the PGM onto a support via incipient wetness impregnation, followed by thermal calcination of the resulting PGM / support mixture. In one example, the mixture is calcined at 400-700°C for 1-3 hours with a ramp rate of 1-25°C / min.

[0071] Chemical immobilization involves deposition of the PGMs on a support followed by immobilization using additional reagents to chemically transform the PGMs. As an example, aqueous Pd-nitrate is impregnated onto alumina. The impregnated powder is not dried or calcined, but instead added to an aqueous solution of Ba-hydroxide. As a result of the addition, the acidic Pd-nitrate reacts with the basic Ba-hydroxide to produce water-insoluble Pd-hydroxide and Ba-nitrate. Thus, Pd is chemically immobilized as an insoluble component in the pores and on the surface of the alumina support. Alternatively, the support can be first impregnated with an acidic component followed by a second basic component. The chemical reaction between the two reagents deposited on the support, e.g., alumina, results in the formation of insoluble or poorly soluble compounds that deposit on the pores and surface of the support.

[0072] Incipient wetness impregnation technique, also called capillary impregnation or dry impregnation, is commonly used for the synthesis of heterogeneous materials, i.e., catalysts. Typically, active metal precursors are dissolved in an aqueous or organic solution, and then the metal-containing solution is added to the catalyst support, which contains a pore volume equal to the volume of the added solution. Capillary action draws the solution into the pores of the support. The solution added beyond the pore volume of the support changes the solution transport from a capillary action process to a much slower diffusion process. The catalyst is dried and calcined to remove volatile components in the solution and deposit the metal on the surface of the catalyst support. The concentration profile of the impregnated material depends on the mass transfer conditions in the pores during impregnation and drying. After appropriate dilution, multiple active metal precursors may be co-impregnated into the catalyst support. Alternatively, the active metal precursors are introduced into the slurry via post-addition under stirring during the process of slurry preparation.

[0073] The support particles are typically sufficiently dry to absorb substantially all of the solution to form a wet solid. Typically, an aqueous solution of a water-soluble compound or complex of the active metal, such as rhodium chloride, rhodium nitrate, rhodium acetate, or combinations thereof (if rhodium is the active metal), and palladium nitrate, palladium tetraamine, palladium acetate, or combinations thereof (if palladium is the active metal), is utilized. After treatment of the support particles with the active metal solution, the particles are dried, such as by heat treating the particles at an elevated temperature (e.g., 100-150°C) for a period of time (e.g., 1-3 hours), and then calcined to convert the active metal to a more catalytically active form. An exemplary calcination process includes heat treatment in air at a temperature of 400-550°C for 10 minutes to 3 hours. If necessary, the above process can be repeated by means of impregnation to reach the desired loading level of the active metal.

[0074] The catalyst composition is typically prepared in the form of catalyst particles as described above. These catalyst particles are mixed with water to form a slurry for the purpose of coating a catalyst substrate, such as a honeycomb substrate. In addition to the catalyst particles, the slurry may optionally contain a binder in the form of alumina, silica, zirconium acetate, zirconia, or zirconium hydroxide, an associative thickener, and / or a surfactant, including anionic, cationic, nonionic, or amphoteric surfactants. Other exemplary binders include boehmite, gamma-alumina, or delta / theta alumina, as well as silica sol. Binders, when present, are typically used in an amount of about 1-5 wt.% of the total washcoat loading. Addition of acidic or basic species to the slurry is performed to adjust the pH. For example, in some embodiments, the pH of the slurry is adjusted by addition of ammonium hydroxide, aqueous nitric acid, or acetic acid. A typical pH range for the slurry is about 3-12.

[0075] The slurry may be milled to reduce particle size and promote particle mixing. Milling may be accomplished in a ball mill, continuous mill, or other similar equipment, and the solids content of the slurry may be, for example, about 20-60% by weight, more specifically, about 20-40% by weight. In one embodiment, the slurry after milling has a D of about 3 to about 40 micrometers, preferably 10 to about 30 micrometers, and more preferably about 10 to about 15 micrometers. 90 Characterized by particle size. D 90 D is determined using a dedicated particle size analyzer. The instrument used in this example uses laser diffraction to measure particle size in small amounts of slurry. D in microns 90 typically means that 90% of the particles by number have a diameter smaller than the quoted value.

[0076] The slurry is coated onto the catalytic substrate using any washcoat technique known in the art. In one embodiment, the catalytic substrate is dipped or otherwise coated with the slurry one or more times. The coated substrate is then dried at an elevated temperature (e.g., 100-150°C) for a period of time (e.g., 10 minutes to 3 hours) and then calcined by heating, for example, at 400-700°C, typically for about 10 minutes to about 3 hours. After drying and calcination, the final washcoat coating layer is believed to be essentially solvent-free. After calcination, the catalyst loading obtained by the above washcoat technique can be determined by calculating the difference between the coated and uncoated weights of the substrate. As will be apparent to one skilled in the art, the catalyst loading can be modified by changing the rheology of the slurry. In addition, the coating / drying / calcining process to produce a washcoat can be repeated as necessary to build the coating to a desired loading level or thickness, i.e., to apply more than one washcoat.

[0077] In certain embodiments, the coated substrate is aged by subjecting the coated substrate to a heat treatment. In one embodiment, aging is performed in a 10% by volume moisture environment at a temperature of about 850° C. to about 1050° C. for 50-75 hours with alternating hydrocarbon / air feeds. Thus, in certain embodiments, an aged catalyst article is provided. In certain embodiments, particularly useful materials include metal oxide-based supports (including, but not limited to, substantially 100% ceria supports) that maintain a high percentage of their pore volume (e.g., about 95-100%) upon aging (e.g., 10% by volume moisture, aging for 50-75 hours with alternating hydrocarbon / air feeds at about 850° C. to about 1050° C.).

[0078] In another aspect, the claimed invention provides an exhaust system for an internal combustion engine, the exhaust system comprising the catalyst article described herein above. In one embodiment, the exhaust system comprises a platinum group metal-based three-way conversion (TWC) catalyst article and a layered catalyst article according to the invention, the platinum group metal-based three-way conversion (TWC) catalyst article being positioned downstream from the internal combustion engine, and the layered catalyst article being positioned downstream in flow communication with the platinum group metal-based three-way conversion (TWC) catalyst article.

[0079] In another embodiment, an exhaust system includes a platinum group metal-based three-way conversion (TWC) catalyst article and a layered catalyst article according to the present invention, the layered catalyst article being positioned downstream from an internal combustion engine and the platinum group metal-based three-way conversion (TWC) catalyst article being positioned downstream in flow communication with the three-way conversion (TWC) catalyst article. The exhaust system is shown in Figures 2B and 2C.

[0080] In one exemplary embodiment, an exhaust system includes a) a layered catalyst article including: i) a first layer including Pd supported on an OSC, Pd supported on alumina, and barium oxide; ii) a second layer including Rh and Pt supported on an OSC, and Pd supported on alumina; and b) a TWC catalyst including: i) a first layer including Pd supported on an OSC and alumina, and barium oxide; ii) a second layer including Rh supported on an alumina and an OSC. The exhaust system is illustrated in FIG. 2B, where a CC1 catalyst IC-1 (catalyst article of the invention) is positioned in fluid communication with the internal combustion engine, and a CC2 catalyst RC-2 (reference CC catalyst) is positioned in fluid communication with the CC1 catalyst.

[0081] FIG. 2A illustrates a baseline exhaust system in which the CC1 RC-1 catalyst includes i) a first layer including OSC and Pd supported on alumina, and barium oxide; and ii) a second layer including Rh supported on alumina and Pd supported on OSC; and the CC2-RC-2 catalyst includes i) a first layer including OSC and Pd supported on alumina, and barium oxide; and ii) a second layer including Rh supported on alumina and Pd supported on OSC.

[0082] In another exemplary embodiment, an exhaust system includes a) a layered catalyst article including: i) a first layer including Pd supported on an OSC, Pd supported on alumina, and barium oxide; and ii) a second layer including Rh supported on an OSC and Pt supported on lanthana-zirconia; and b) a TWC catalyst including: i) a first layer including Pd supported on an OSC and alumina, and barium oxide; and ii) a second layer including Rh supported on alumina and OSC. The exhaust system is illustrated in FIG. 2C, where CC1 catalyst IC-2 (catalyst article of the present invention) is positioned in fluid communication with the internal combustion engine, and CC2 catalyst RC-2 (reference CC catalyst) is positioned in fluid communication with CC1 catalyst.

[0083] In another aspect, the claimed invention also provides a method for treating a gaseous exhaust stream, including hydrocarbons, carbon monoxide, and nitrogen oxides. The method includes contacting the exhaust stream with a catalyst article or an exhaust system according to the claimed invention. The terms "exhaust stream", "engine exhaust stream", "exhaust gas stream", and the like refer to any combination of flowing engine outflow gases, which may also contain solid or liquid particulate matter. The stream is, for example, the exhaust of a lean-burn engine, which includes gaseous components and may also contain certain non-gaseous components, such as liquid droplets, solid particles, and the like. The exhaust stream of a lean-burn engine typically includes products of combustion, products of incomplete combustion, oxides of nitrogen, combustible and / or carbonaceous particulate matter (soot), and unreacted oxygen and / or nitrogen. Such terms similarly refer to the downstream effluent of one or more other catalyst system components as described herein. In one embodiment, a method is provided for treating an exhaust stream containing carbon monoxide.

[0084] In another aspect, the claimed invention also provides a method for reducing the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a catalytic article or exhaust system according to the claimed invention to reduce the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in the exhaust gas.

[0085] In yet another aspect, the claimed invention also provides the use of the catalytic article of the claimed invention to purify a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides.

[0086] In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of carbon monoxide, hydrocarbons, and nitrous oxides present in the exhaust gas stream prior to contact with the catalytic article. In some embodiments, the catalytic article converts the hydrocarbons to carbon dioxide and water. In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of hydrocarbons present in the exhaust gas stream prior to contact with the catalytic article. In some embodiments, the catalytic article converts carbon monoxide to carbon dioxide. In some embodiments, the catalytic article converts nitrogen oxides to nitrogen.

[0087] In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of nitrogen oxides present in the exhaust gas stream prior to contact with the catalytic article. In some embodiments, the catalytic article converts at least about 50%, or at least about 60%, or at least about 70%, or at least about 80%, or at least about 90%, or at least about 95% of the total amount of combined hydrocarbons, carbon dioxide, and nitrogen oxides present in the exhaust gas stream prior to contact with the catalytic article. EXAMPLES

[0088] Aspects of the present invention are more fully illustrated by the following examples, which are set forth to illustrate certain specific aspects of the invention and should not be construed as limiting thereof.

[0089] Example 1: Preparation of a reference catalyst article (CC1 RC-1, bimetallic catalyst: Pd:Rh (1:0.052)) The Pd / Rh based TWC catalyst article was prepared as a close-coupled catalyst. The total PGM loading (Pd / Pt / Rh) was 76 / 0 / 4. The bottom coat was 68.4 g / ft 3 of Pd, or 90% of the total Pd in ​​the catalyst. The topcoat contains 7.6 g / ft 3 of Pd, and 4g / ft 3 of Rh, or 10% of the total Pd and 100% of the total Rh in the catalyst. The bottom coat is 2.34 g / in. 3 and the topcoat has a washcoat loading of 1.355 g / in. 3 The bottom coat was prepared by impregnating 314 grams of alumina with a 60% Pd-nitrate solution (43.3 grams, 28% aqueous Pd-nitrate solution) and 785 grams of ceria-zirconia with a 40% Pd-nitrate solution (28.9 grams, 28% aqueous Pd-nitrate solution). The alumina portion was chemically fixed by adding the Pd / alumina mixture to an aqueous solution of 85.6 grams of barium acetate in water. 39 grams of barium sulfate were also added to the mixture. This component was then mixed to obtain a D below 16 μm. 90 The ceria-zirconia portion was added to water and ground to a D below 16 μm. The pH was controlled at about 4-5 by addition of nitric acid, if necessary. 90 The mixture was ground to pH 4. If necessary, the pH was controlled at about 4-5 by the addition of nitric acid. The two components were then blended and 128 grams of alumina binder was added to the blend.

[0090] The topcoat has two components. The first component was prepared by impregnating a mixture of 20.7 grams of Rh nitrate (9.9% Rh content) and 80.5 grams of neodymium nitrate (27.5% Nd2O3 content) in 560 grams of water onto 903 grams of alumina. This step was followed by a calcination at 500°C for 2 hours to allow the fixing of the PGMs on the support. The resulting powder was then mixed with water and refined to a D below 16 μm. 90The second component was prepared by impregnating 13.8 grams of Pd nitrate (28% Pd content) mixed with water onto 260.4 grams of ceria-zirconia, followed by calcination at 500° C. for 2 hours to allow PGM immobilization on the support. The resulting powder was then mixed with water and ground to a D below 16 μm. 90 The mixture was ground to a pH of about 4-5. If necessary, the pH was controlled to about 4-5 by the addition of nitric acid. The two slurries thus obtained were combined and 156 grams of alumina binder was added. If necessary, the pH was controlled to about 4-5 by the addition of nitric acid. A catalyst article was prepared by first coating the bottom coat slurry onto a 600 / 3.5 ceramic substrate. The resulting coated substrate was then dried and calcined at 500° C. for 2 hours. A second (top coat) slurry was then applied. The resulting product was again calcined at 500° C. for 2 hours.

[0091] Example 2: Preparation of a catalyst article of the present invention (CC 1 IC-A, trimetallic-Pd, Pt and Rh in the top layer and Pd in ​​the bottom layer (ratio: 1.0:1.0:0.105), heat set) The catalyst article was formulated using Pd, Pt, and Rh to produce a 38 / 38 / 4 design. The total PGM loading was 80g / ft 3 and the bottom coat is 30.4 g / ft 3 of Pd, or 80% of the total Pd in ​​the catalyst. The topcoat contains 7.6 g / ft 3 Pd, 38g / ft 3 of Pt, and 4g / ft 3 Contains 20% of the total Pd in ​​the catalyst, 100% of the total Pt and Rh. The bottom coat is 2.318 g / in. 3 and the topcoat has a washcoat loading of 1.352 g / in. 3The bottom coat was prepared by impregnating 396 grams of alumina with a 60% Pd-nitrate solution (24.3 grams, 28% aqueous Pd-nitrate solution) and 990.6 grams of ceria-zirconia with a 40% Pd-nitrate solution (16.2 grams, 28% aqueous Pd-nitrate solution). The alumina portion was chemically fixed by adding the Pd / alumina mixture to an aqueous solution of 108 grams of barium acetate in water. 49.3 grams of barium sulfate were also added to the mixture. This component was then mixed to obtain a 16 μm D 90 The pH was controlled at about 4-5 by addition of nitric acid, if necessary. The ceria-zirconia portion was added to water and ground to a D below 16 μm. 90 The mixture was ground to pH 4. If necessary, the pH was controlled at about 4-5 by the addition of nitric acid. The two components were then blended and 161 grams of alumina binder was added.

[0092] The topcoat has two components. The first component was prepared by impregnating a mixture of 17.3 grams of Pd nitrate (28% Pd content) in 200 grams of water onto 283 grams of alumina. This step was followed by calcination at 500° C. for 2 hours to allow the fixing of the PGMs on the support. The resulting powder was then mixed with water and refined to a D below 16 μm. 90 The second component was prepared by impregnating 1175.4 grams of ceria-zirconia with 170.9 grams of Pt nitrate (14.3% Pt content) and 25.9 grams of Rh nitrate (9.9% Rh content) mixed with water, followed by calcination at 500°C for 2 hours to allow PGM immobilization on the support. The resulting powder was then mixed with water and ground to a size below 16 μm. 90The mixture was ground to a pH of about 4-5 by addition of nitric acid, if necessary. The two slurries thus obtained were blended and 194 grams of alumina binder was added. If necessary, the pH was controlled to about 4-5 by addition of nitric acid. A catalytic article was prepared by first coating the bottom coat slurry onto a 600 / 3.5 ceramic substrate. The resulting coated substrate is then dried and calcined at 500°C for 2 hours. A second, top coat, slurry is then applied and the resulting product is again calcined at 500°C for 2 hours. Comparative testing showed that the catalytic article of the present invention exhibits improved reduction of THC, NO, and CO compared to the reference catalytic article RC-1. The results are shown in the attached figures.

[0093] Example 3: Preparation of a catalytic article of the present invention (CC 1 IC-B, trimetallic-Pt and Pd in ​​separate layers (top layer: Rh+Pt, bottom layer: Pd, ratio: 1.0:1.0:0.105) The catalyst article was formulated using Pd, Pt, and Rh to produce a 38 / 38 / 4 design. The total PGM loading was 80g / ft 3 and the bottom coat is 38 g / ft 3 of Pd, or 100% of the total Pd in ​​the catalyst. The topcoat contains 38 g / ft 3 of Pt and 4g / ft 3 of Rh, or 100% of the total Pt and Rh in the catalyst. The bottom coat contains 2.322 g / in 3 and the topcoat had a washcoat loading of 1.347 g / in. 3The bottom coat was prepared by impregnating 395.5 grams of alumina with a 60% Pd-nitrate solution (30.3 grams, 28% aqueous Pd-nitrate solution) and 988.8 grams of ceria-zirconia with a 40% Pd-nitrate solution (20.2 grams, 28% aqueous Pd-nitrate solution). The alumina portion was chemically fixed by adding the Pd / alumina mixture to an aqueous solution of 108 grams of barium acetate in water. 49.2 grams of barium sulfate were also added to the mixture. This component was then mixed to obtain a 16 μm D 90 The ceria-zirconia portion was added to water and ground to a D below 16 μm. The pH was controlled at about 4-5 by addition of nitric acid, if necessary. 90 The mixture was ground to pH 4.0. If necessary, the pH was controlled at about 4-5 by the addition of nitric acid. The two components were then blended and 161.5 grams of alumina binder was added.

[0094] The topcoat has two components. The first component was prepared by impregnating a mixture of 26 grams of Rh nitrate (9.9% Rh content) in 320 grams of water onto 731.6 grams of ceria-zirconia. This step was followed by calcination at 500° C. for 2 hours to allow for the fixation of the PGMs on the support. The second component was prepared by impregnating 171.4 grams of Pt nitrate (14.3% Pt content) mixed with water onto 731.6 grams of lanthana-zirconia, followed by calcination at 500° C. for 2 hours to allow for the fixation of the PGMs on the support. The two-component powder was then mixed with water and quenched to a D below 16 μm. 90The slurry thus obtained was mixed with 194.8 grams of alumina binder. If necessary, the pH was controlled to about 4-5 by the addition of nitric acid. The catalytic articles were prepared by first coating the bottom coat slurry onto a 600 / 3.5 ceramic substrate. The resulting coated substrate was then dried and calcined at 500° C. for 2 hours. Then, a second (top coat) slurry was applied. The resulting product was again calcined at 500° C. for 2 hours. The catalytic articles A and B of the present invention are illustrated in FIG. 1A and FIG. 1B, while the reference catalytic article is illustrated in FIG. 1C of the accompanying drawings. Comparative tests showed that the catalytic articles of the present invention show improved reduction of THC, NO, and CO compared to the reference catalytic article RC-1. The results are shown in the accompanying figures.

[0095] Example 4: Preparation of Catalyst Articles (Catalyst Article C, Catalyst Article D, and Catalyst Article E, Pd / Pt in the Underlayer with Variation of Support, Out of Scope) Catalyst articles C, D, and E were prepared to confirm the effectiveness of direct substitution of Pt for Pd in ​​the reference CC TWC design. Substitution was performed by replacing 50% Pd with 50% Pt on a weight basis. The catalyst designs are provided in the table below. [Table 1]

[0096] The bottom coat of catalyst article C was prepared by using a Pd / Pt mixture equally divided between alumina and ceria-zirconia, while the top coat was kept the same as that of the reference catalyst, i.e., the top coat contained Pd on ceria-zirconia and Rh on alumina. The bottom coat of catalyst article D was prepared using Pd on ceria-zirconia and Pt on alumina, while the top coat was prepared using Rh on ceria-zirconia and Pt on alumina. The bottom coat of catalyst article E was prepared using Pd on alumina and Pt on ceria-zirconia, while the top coat was prepared using Rh on ceria-zirconia and Pt on alumina. The washcoat loading was kept the same as in the reference.

[0097] The catalysts were prepared by first coating the bottom coat slurry onto a 600 / 3.5 ceramic substrate. The resulting coated substrate was then dried and calcined at 500° C. for 2 hours. A second (top coat) slurry was then applied. The resulting product was again calcined at 500° C. for 2 hours. Comparative testing showed that catalyst articles C, D and E exhibited lower reductions of THC, NO and CO compared to the reference catalyst article RC-1. The results are shown in the attached figures.

[0098] Example 5: Preparation of a second close-coupled TWC reference catalyst article (CC2 RC-2 catalyst article) A reference CC2 TWC catalyst article (Pd / Pt / Rh: 14 / 0 / 4) was prepared and used in all the following examples in the second proximal bond position. The bottom coat was prepared by mixing 718.5 grams of alumina with water, controlling the pH to about 4-5 by the addition of nitric acid, followed by addition of 16 μm D 90 The slurry was prepared by grinding to a particle size of less than 14 μm. Then, 716.2 grams of ceria-zirconia was added to the slurry. Then, 27.7 grams of Pd (Pd content of 27.3%) was added to the slurry and after mixing for a short time, the slurry was ground to a particle size of less than 14 μm. 90In the next step, 71.5 grams of barium sulfate and 239.2 grams of alumina binder were added and the final slurry was mixed for 20 minutes.

[0099] The topcoat is made of two components. The first component was prepared by impregnating 11.3 grams of Rh nitrate in 367 grams of water (Rh content of 9.8%) onto 483 grams of alumina. The powder was then added to water and methyl-ethyl-amine (MEA) was added until the pH was 8. The slurry was then mixed for 20 minutes and the pH was reduced to 5.5-6 using nitric acid. The slurry was then mixed to remove 14 μm D. 90 The second component was prepared by impregnating 11.3 grams of Rh nitrate (9.8% Rh content) mixed with 550 grams of water onto 979.3 grams of ceria-zirconia. The powder was then added to water and methyl-ethyl-amine (MEA) was added until the pH was 8. The slurry was then mixed for 20 minutes. If necessary, 80.6 grams of zirconium nitrate (19.7% ZrO2 content) was added to it and the pH was reduced to 5.5-6 using nitric acid. The slurry was then ground to a D below 14 μm. 90 The two resulting slurries were then blended, if necessary, and 245 grams of alumina binder was added and the pH was controlled at about 4-5 by the addition of nitric acid.

[0100] The catalyst articles were prepared by first coating the bottom coat slurry onto a 600 / 3.5 ceramic substrate. The resulting coated substrate was then dried and calcined at 500° C. for 2 hours. A second (top coat) slurry was then applied. The resulting product was again calcined at 500° C. for 2 hours.

[0101] Example 6: Preparation of catalyst system A of the present invention and its testing (CC1 IC-A+CC2 RC-2): Catalyst system A consisting of catalyst article A of the present invention (Pd / Pt / Rh: 38 / 38 / 4) and reference CC2 catalyst article (Pd / Pt / Rh: 14 / 0 / 4) was prepared and compared with a reference system consisting of reference CC1 catalyst article (Pd / Pt / Rh: 76 / 0 / 4) and reference CC2 catalyst article (Pd / Pt / Rh: 14 / 0 / 4). Catalyst system A is shown in FIG. 2B, while the reference system is shown in FIG. 2A. Both systems were aged at 950° C. for 50 hours under alternating feed conditions and then engine tested using the FTP-75 test protocol in a SULEV-30 certified light vehicle. The claimed catalyst system A reduced THC, CO, and NO in the midbed by 17% compared to the reference system by 20%. x and 20% THC, 24% CO, and 18% NO in the tailpipe. x The results demonstrate improved TWC performance with an improvement in TWC performance. Thus, the 38 / 38 / 4 trimetallic catalyst not only meets the performance of the Pd / Rh 0 / 76 / 4 standard, but also provides an improvement over the standard. The results are shown in Figures 4A, 4B, and 4C.

[0102] Example 7: Preparation of catalyst system B of the present invention and its testing: (CC1 IC-B + CC2 RC-2) A system consisting of the catalyst article B of the present invention (Pd / Pt / Rh: 38 / 38 / 4) and the reference CC2 catalyst article (Pd / Pt / Rh: 14 / 0 / 4) was prepared and compared to a reference system consisting of the reference CC1 catalyst article (Pd / Pt / Rh: 76 / 0 / 4) and the CC2 catalyst article (Pd / Pt / Rh: 14 / 0 / 4). Catalyst system B is shown in FIG. 2C. Both systems were aged at 980° C. for 12 hours under alternating feed conditions and then reactor tested using a reactor simulation in a SULEV-30 certified light vehicle. The reactor is set so that the lambda, temperature, and rate traces match those of the vehicle under FTP-72 test conditions. The claimed system B demonstrates improved TWC performance with an improvement of 21% THC, 33% CO, and 28% NO, representing the midbed results. The results are shown in FIG. 3.

[0103] The catalyst system design is provided in the table below. [Table 2]

[0104] Research findings / results From the results shown in the above examples and figures, it is found that directly incorporating platinum into existing Pd / Rh catalysts by replacing 50% of Pd with Pt is not the most efficient way towards Pt utilization. As shown in Example 4 and Figures 5A, 5B, and 5C, this approach typically results in up to a 30% increase in emissions of hydrocarbons, CO, and nitrous oxide, depending on the emission type. Moreover, this increase occurs regardless of whether Pt and Pd are mixed on the same support or present on different supports, unless there is thermal or chemical fixation of each metal prior to catalyst washcoating.

[0105] The aforementioned shortcomings are resolved in the claimed catalyst articles A and B (Examples 2 and 3) of the present invention, where Pd and Pt are allocated to different support types and / or different layers of the catalyst article. Pd and Pt can be present in the same layer (invention catalyst article B), as long as the metals are chemically or thermally fixed prior to slurry coating. Both designs demonstrate improvements over the reference system, typically in the range of 20-30%, for the reported examples, emission type dependent. The improvements are in both the midbed as well as the tailpipe, demonstrating the activity of the Pt-containing system itself, and not a compensating effect from the CC2 catalyst article. The results are shown in Figures 3, 4, and 6.

[0106] References throughout this specification to "one embodiment," "a particular embodiment," "one or more embodiments," or "embodiments" mean that a particular feature, structure, material, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearance of phrases such as "in one or more embodiments," "in a particular embodiment," "in some embodiments," "in one embodiment," or "in an embodiment" in various places throughout this specification do not necessarily refer to the same embodiment of the invention. Furthermore, particular features, structures, materials, or characteristics can be combined in any suitable manner in one or more embodiments. All of the various embodiments, aspects, and options disclosed herein can be combined in all variations, regardless of whether such features or elements are explicitly combined in the description of a particular embodiment herein. The present invention is intended to be read as a whole, and should be considered to be intended to contemplate that any separable features or elements of the disclosed invention are combinable in any of its various aspects and embodiments, unless the context clearly indicates otherwise.

[0107] Although the embodiments disclosed herein have been described with reference to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the present invention. It will be apparent to those skilled in the art that various modifications and changes can be made to the method and apparatus of the present invention without departing from the spirit and scope of the present invention. Therefore, the present invention is intended to include modifications and changes that come within the scope of the appended claims and their equivalents, and the above embodiments are presented for purposes of illustration and not limitation. All patents and publications cited in this specification are incorporated herein by reference for their specific teachings, as described, unless other incorporation statements are specifically provided.

Claims

1. a) a first layer comprising palladium supported on both an oxygen storage component and an alumina component; b) a second layer comprising platinum and rhodium, each supported on at least one of the oxygen storage component and the zirconia component; c) a substrate, the weight ratio of palladium to platinum throughout the trimetallic layered catalyst article is in the range of 1.0:0.4 to 1.0:2.0; the first layer is deposited on the substrate and the second layer is deposited on the first layer; the oxygen storage component of the first and second layers comprises ceria-zirconia, ceria-zirconia-lanthana, ceria-zirconia-yttria, ceria-zirconia-lanthana-yttria, ceria-zirconia-neodymia, ceria-zirconia-praseodymia, ceria-zirconia-lanthana-neodymia, ceria-zirconia-lanthana-praseodymia, ceria-zirconia-lanthana-neodymia-praseodymia, or any combination thereof; the alumina component comprises alumina, lanthana-alumina, ceria-alumina, ceria-zirconia-alumina, zirconia-alumina, lanthana-zirconia-alumina, baria-alumina, baria-lanthana-alumina, baria-lanthana-neodymia-alumina, or a combination thereof; the zirconia component is selected from the group consisting of lanthana-zirconia, barium-zirconia, and combinations thereof; and the first layer is essentially free of platinum and rhodium; the second layer further comprises palladium supported on an alumina component, whereby the palladium and platinum in the second layer are supported on separate supports, and the palladium and platinum are chemically or thermally fixed to the respective supports prior to slurry coating; A trimetallic layered catalyst article for the conversion of CO, HC and NOx in exhaust gases from an internal combustion engine.

2. The layered catalyst article of claim 1, wherein the weight ratio of palladium to platinum in the entire trimetallic layered catalyst article is in the range of 1.0:0.7 to 1.0:1.

3.

3. The layered catalyst article of claim 1, wherein the weight ratio of palladium to platinum in the entire trimetallic layered catalyst article is 1.0:1.

0.

4. The layered catalyst article of claim 1, wherein the weight ratio of palladium to platinum to rhodium throughout the trimetallic layered catalyst article is in the range of 1.0:0.7:0.1 to 1.0:1.3:0.

3.

5. The layered catalyst article of any one of claims 1 to 4, wherein the first layer comprises 80 to 100 weight percent palladium based on the total amount of palladium present in the catalyst article.

6. The layered catalyst article of any one of claims 1 to 5, wherein the amount of the oxygen storage component is from 20 to 80 weight percent, based on the total weight of the first layer.

7. The layered catalyst article of any one of claims 1 to 6, wherein the amount of said alumina component is from 10 to 90 weight percent, based on the total weight of said first layer.

8. 8. The layered catalyst article of any one of claims 1 to 7, wherein the first layer comprises at least one alkaline earth metal oxide comprising barium oxide, strontium oxide, or any combination thereof in an amount of 1.0 to 20 wt%, based on the total weight of the first layer.

9. The layered catalyst article of any one of claims 1 to 8, wherein the zirconia component comprises at least 70 weight percent zirconia, based on the total weight of the zirconia component.

10. 10. The layered catalyst article of any one of claims 1 to 9, wherein the oxygen storage component of the first layer comprises ceria in an amount of 20 to 50 weight percent, based on the total weight of the oxygen storage component, while the oxygen storage component of the second layer comprises ceria in an amount of 5 to 15 weight percent, based on the total weight of the oxygen storage component.

11. 11. The layered catalyst article of any one of claims 1 to 10, wherein the second layer further comprises palladium supported on an alumina component, the amount of palladium being 0.1 to 20% based on the total weight of palladium present in the catalyst article.

12. The first layer is a 1.0 to 300 g / ft2 alumina component and an oxygen storage component supported thereon. 3 (35.3~10594.4g / m 3 ) palladium, and said second layer is filled with 1.0-100 g / ft 3 (35.3~3531.5g / m 3 ) of rhodium and 1.0 to 300 g / ft 3 (35.3~10594.4g / m 3 12. The layered catalyst article of any one of claims 1 to 11, wherein said catalyst is loaded with at least one of platinum and at least one of zirconia and oxygen storage component.

13. 13. The layered catalyst article of any one of claims 1 to 12, wherein the first layer comprises the oxygen storage component and palladium supported on the alumina component, and the second layer comprises rhodium and platinum, each supported on the oxygen storage component, and palladium supported on the alumina component.

14. 14. The layered catalyst article of any one of claims 1 to 13, wherein the first layer comprises palladium supported on the oxygen storage component and an alumina component, and the second layer comprises rhodium supported on the oxygen storage component and platinum supported on the zirconia component.

15. The layered catalyst article of any one of claims 1 to 14, wherein the substrate is a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymeric foam substrate, or a woven fiber substrate.

16. The layered catalyst article of any one of claims 1 to 15, wherein the platinum and / or palladium is thermally or chemically fixed.

17. 17. A process for the preparation of a layered catalyst article according to any one of claims 1 to 16, comprising: preparing a first layer slurry; depositing the first layer slurry on a substrate to obtain a first layer; preparing a second layer slurry; and depositing the second layer slurry on the first layer to obtain a second layer followed by calcination at a temperature in the range of 400 to 700°C, wherein the step of preparing the first layer slurry or the second layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation, and post-addition.

18. An exhaust system for an internal combustion engine, said system comprising a layered catalyst article according to any one of claims 1 to 16.

19. 19. The exhaust system of claim 18, wherein the system comprises a platinum group metal based three-way conversion (TWC) catalyst article and the layered catalyst article of any of claims 1-16, wherein the platinum group metal based three-way conversion (TWC) catalyst article is positioned downstream of an internal combustion engine, and the layered catalyst article is positioned downstream in flow communication with the platinum group metal based three-way conversion (TWC) catalyst article.

20. 19. The exhaust system of claim 18, wherein the system comprises a platinum group metal based three-way conversion (TWC) catalyst article and the layered catalyst article of any of claims 1-16, the layered catalyst article being positioned downstream of an internal combustion engine, and the platinum group metal based three-way conversion (TWC) catalyst article being positioned downstream in flow communication with the layered catalyst article.

21. 21. A method for treating a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides, said method comprising contacting said exhaust stream with the layered catalyst article of any one of claims 1-16 or the exhaust system of any one of claims 18-20.

22. 21. A method for reducing hydrocarbon, carbon monoxide, and nitrogen oxide levels in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a layered catalyst article according to any one of claims 1-16, or an exhaust system according to any one of claims 18-20, to reduce the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in the exhaust gas.

23. Use of a catalytic article according to any one of claims 1 to 16 for purifying a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides.

Citation Information

Patent Citations

  • Catalyst for purifying exhaust gas and its use

    JP1999104493A

  • Exhaust gas purifying catalyst

    JP1999151439A

  • A metal plate that exhibits catalytic activity

    JP2001524018A

  • Layered catalyst for exhaust treatment

    JP2008503345A

  • Carbon monoxide conversion catalyst

    JP2013521121A